Kindness in the Classroom: Evaluating the Impact of Direct Kindness Instruction on School and Emotional Outcomes in Second-Grade Students - Verba, Braelyn; Vu, Phu (The Canadian Journal of Action Research, 2024)
This study explores the effects of direct kindness instruction on second-grade students' social and emotional well-being. Amidst the growing integration of Social and Emotional Learning (SEL) into educational curricula, this research specifically focuses on the aspect of kindness, a vital yet often under-explored component of SEL. Conducted in a diverse second-grade classroom in a small Midwestern U.S. town, this study employs an action research methodology, using the Second Step curriculum and weekly kindness missions as interventions. The research is guided by two primary questions: the influence of direct kindness instruction on students' social behavior and its impact on their emotional well-being. The effectiveness of the interventions is evaluated using the Social Academic and Emotional Behavior Risk Screener (SABERS). Findings indicate significant improvements in students' academic, social, and emotional behaviors, underscoring the effectiveness of kindness instruction in enhancing the overall educational environment. The study highlights the need for incorporating structured SEL components, particularly kindness and empathy, in early education, and suggests future research directions for exploring long-term impacts of SEL interventions.